Photoelectron spectroscopy and electronic structures of β-diketonate complexes of rare-earth elements - Vovna, V. I.; Korochentsev, V. V.; Cherednichenko, A. I.; Shurygin, A. V. (Russian chemical bulletin, 2015)
The electronic structures of lanthanide tris(β-diketonate) complexes and their adducts, being of interest as luminophores, were studied by UV photoelectron spectroscopy of vapors and X-ray photoelectron spectroscopy. The spectral regularities identified by the density functional theory revealed the influence of the substitution of the Me groups in the ligands by Bu t , CF 3 , and neutral ligand in the adducts on the electronic structure of the complexing agent from Pr to Lu.